Does ultrasound measurement improve the accuracy of electronic brachytherapy in the treatment of superficial non-melanomatous skin cancer? - Goyal, Uma; Pan, Junhan; Cui, Haiyan; Stea, Baldassarre (Journal of Contemporary Brachytherapy, 2017)
Purpose: Electronic brachytherapy (eBT) is a form of contact radiation therapy used for thin superficial non-melanomatous skin cancers (NMSCs). An accurate measurement of diameter and depth is important for eBT treatment planning. Therefore, we compared clinical measurements by an experienced physician to measurements obtained using ultrasound (US), an objective imaging modality, in order to determine if clinical measurements were accurate enough for adequate NMSC treatment. Material and methods : Eighteen patients with 20 biopsy-proven NMSCs first had a clinical examination and then an US evaluation prior to starting eBT. One physician provided a clinical measurement for diameter and depth based on physical examination during radiation oncology consultation. The patients then had an US evaluation with a 14 or 18 MHz US unit, to determine both the diameter and depth measurements; eBT dose prescription was done using the US derived measurements. The clinical measurements and US measurements were compared using a t-test. Results: Seventeen lesions were basal cell carcinoma and 3 lesions were squamous cell carcinoma. The most common location was the nose (10 lesions). The difference between the clinical and the US derived measurements for the second largest diameter was found to be statistically significant (p = 0.03), while the difference for the largest diameter of the lesions was not (p = 0.24). More importantly, the depth measurements obtained with US were also found to be significantly different from the clinical estimates (p = 0.02). All patients have had a complete response to therapy with a median follow-up of 24 months. Conclusions : Statistically different measurements were obtained in 2 of 3 parameters used in choosing applicator size and prescription depth using an US assessment. The data presented suggests that US is a more objective modality than clinical judgment for determining superficial NMSC diameter and prescription depth for personalized eBT planning.